Effect of Financial Distress, Capital Intensity, and Corporate Social Responsibility on Tax Aggressiveness (Study on Manufacturing Companies Listed on the Indonesia Stock Exchange in 2019-2024) - Angraeni, Dea; Suhendar, Suhendar; Etika, Citra (Indonesian Journal of Islamic Economics and Finance, 2025)
The purpose of this study was to determine whether financial distress, capital intensity and corporate social responsibility affect tax aggressiveness. The theory used in this study is the theory of agency. This study uses secondary data obtained using the method of document study. The population in this study is all manufacturing companies listed on the Indonesia Stock Exchange during the period 2019-2024. Sample selection in this study using purposive sampling method. The number of companies that have this criterion is 17 companies. Multiple linear regression analysis technique used as a data analysis technique using SPSS version 25. The results showed that financial distress has a negative and significant effect on tax aggressiveness. Capital intensity has a positive and significant effect on tax aggressiveness. Corporate social responsibility has a negative and significant effect on tax aggressiveness. Financial distress, capital intensity and corporate social responsibility simulatedly affect tax aggressiveness. In previous studies provide inconsistent results so this research is important to do in order to find results that are relevant to the current policy.